The Effect of Ezetimibe/Statin Combination and High-Dose Statin Therapy on Thyroid Autoimmunity in Women with Hashimoto’s Thyroiditis and Cardiovascular Disease: A Pilot Study - Krysiak, R.; Szkróbka, W.; Okopień, B. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Background: Intensive statin therapy was found to reduce thyroid autoimmunity in women with Hashimoto’s thyroiditis. No similar data are available for other hypolipidemic agents.Methods: The participants of the study were 16 women with Hashimoto’s thyroiditis and coronary artery disease. On the basis of statin tolerance, they were divided into 2 groups. 8 patients who did not tolerate high-dose statin therapy were treated with a statin, the dose of which was reduced by half, together with ezetimibe. The remaining 8 patients tolerating the treatment continued high-dose statin therapy. Plasma lipids, serum levels of thyrotropin, free thyroxine and free triiodothyronine, as well as titers of thyroid peroxidase and thyroglobulin antibodies were measured at the beginning of the study and 6 months later.Results: Replacing high-dose statin therapy with ezetimibe/statin combination therapy increased serum titers of thyroid peroxidase as well as led to an insignificant increase in serum titers of thyroglobulin antibodies. At the end of the study, thyroid peroxidase and thyroglobulin antibody titers were higher in patients receiving the combination therapy than in those treated only with high-dose statin.Conclusions: Our study shows that high-dose statin therapy produces a stronger effect on thyroid autoimmunity than ezetimibe/statin combination therapy.
Keywords: cardiovascular disease; ezetimibe; statins; thyroid autoimmunity